Pengaruh Pendidikan Aqidah Akhlak Terhadap Kepribadian Siswa Kelas V Di MIS Mathlail Khoir, Kecamatan Bojong Gede, Kabupaten Bogor - Afrina, Amelia; Aminah, Siti; Hadi, Sholikul (Ikatan Dai Indonesia, 2023)
Aqidah moral education is a means in the formation of a good personality. The formation of personality that is applied in schools is needed to instill an understanding in a child, that a good personality will produce good character, all forms of attitude and behavior, both good and bad, will become a moral person, the responsibility of every human being in everyday life. in this world and in the hereafter. This study was conducted to determine whether there is an influence of moral aqidah education on the personality of fifth grade students at MIS Mathlail Khoir, this type of research uses quantitative research methods that are descriptive analysis with a total sample of 54 students and the sampling technique is Saturated Sampling as many as 54 students who assigned to students. These instruments are observation, documentation and questionnaires. The method of data analysis was carried out by a simple linear regression technique. Based on the data analysis that has been carried out, the results of the study indicate that the education of moral aqidah and personality of the students in the school is said to be high with a mean value of X 52.93 while Y 43.80. And it shows that there is a significant influence between moral aqidah education on students' personality from the regression equation obtained by Y' = 7.419 + 0.687 X showing that there is a positive or unidirectional relationship, based on the calculation of the coefficient of determination of 34.8% while 65.2% is influenced by by other variables not examined.